A Siberian history of Soviet film manufacturing visions of the indigenous peoples of the north - Damiens, Caroline 1974- (KINO: the Russian and Soviet cinema, 2024)
"This book delves into the representation of the indigenous "Peoples of the North" in Soviet cinema and TV from the 1920s to the 1980s. It traces their evolving depictions, which shifted between portraying them as backward and in harmony with nature, reflecting the Soviet Union's evolving perception of modernity. Caroline Damiens combines a detailed analysis of key works such asTymancha’s Friend(1969),The Most Beautiful Ships(1972),Tracking the Wolverine(1978) andWhen the Whales Leave(1981), with primary sources like press articles, archives, and interviews, to reveal how these cinematic portrayals were created and negotiated, providing insight into the concepts of progress and authenticity in the Soviet context. She emphasizes the role of indigenous individuals in shaping their cinematic image, both in front of and behind the camera, highlighting the works of lesser-known figures like Suntsai Geonka, Zinaida Pikounova, and Iurii Rytkheu. In doing so, Damiens emphasizes the multifaceted nature of film, where interpretations differ based on the perspectives of those involved. Using a de-colonial approach and drawing from extensive archival materials, Damiens prompts a re-evaluation of the Soviet cinematic past and present by centering indigenous voices in the narrative. In doing so, she provides a thorough exploration of the intricate relationship between culture, representation, and identity in Soviet cinema."